1998
DOI: 10.1590/s0006-87051998000200020
|View full text |Cite
|
Sign up to set email alerts
|

Resposta Do Feijoeiro a Doses De Boro Em Cultivo De Inverno E De Primavera

Abstract: Um experimento em vasos foi instalado em casa de vegetação com o objetivo de estudar a resposta do feijoeiro à aplicação de boro (B) em solo com baixa disponibilidade desse nutriente. Os tratamentos consistiram na aplicação de doses correspondentes a 0, 1, 2, 4, 8 e 16 kg.ha-1 de B, na forma de bórax. Dois ensaios foram desenvolvidos, sendo o primeiro no inverno (junho a julho) e o outro na primavera (setembro a outubro). No ensaio do inverno, foi observada a deficiência de B, apenas na testemunha, fato compro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
0
1
1
Order By: Relevance
“…However, the increase obtained in the number of grains per pod a result of borated fertilization up to the 1.31 kg ha -1 B rate was not reflected in bean productivity growth. This result is inconsistent with other studies (Mascarenhas et al, 1998;Mariano et al, 1999;Souza et al, 2011), which found a positive response by bean plants to borated fertilization, certainly due to the supply of the plant nutritional needs for boron directly from the soil.…”
Section: Agronomic Aspects Of Cropscontrasting
confidence: 99%
“…However, the increase obtained in the number of grains per pod a result of borated fertilization up to the 1.31 kg ha -1 B rate was not reflected in bean productivity growth. This result is inconsistent with other studies (Mascarenhas et al, 1998;Mariano et al, 1999;Souza et al, 2011), which found a positive response by bean plants to borated fertilization, certainly due to the supply of the plant nutritional needs for boron directly from the soil.…”
Section: Agronomic Aspects Of Cropscontrasting
confidence: 99%
“…Avaliando, por meio da produção de matéria seca em dois cultivos, MASCARENHAS et al (1998) obtiveram dados semelhantes, em outra cultura, aos apresentados neste trabalho, ou seja, verificaram queda linear na produção de matéria seca na cultura do feijoeiro submetidos à aplicação de doses de 0 até 16 kg ha -1 de B, em solo com pH CaCl 2 de 6,3. Em relação à produção de matéria seca do sistema radicular, não houve diferença significativa entre as cultivares (Figura 1d).…”
Section: Resultsunclassified